USING THE MIND PALACE TECHNIQUE FOR LEARNING ENGLISH COLLOCATIONS AND IDIOMS - Shakurova Nargiza; Nusratova Mahbuba (Modern American Journals, 2025)
This article explores using an effective mnemonic technique called the Mind Palace (or Method of Loci) to learn English collocations and idioms. Knowing idioms and collocations is crucial for developing and improving writing and speaking skills, but foreign language learners struggle with memorizing them because of their figurative meanings and contextual variations. Sherlock Holmes, the most famous fictional detective known for his unique intelligence, popularized this method. Learning collocations and idioms in connection with a familiar environment is more effective than traditional memorizing methods (repeating, rote learning, and word lists). This study reviews the theoretical foundations of this method. It highlights the way of using this strategy to learn foreign languages and the practical steps for designing individual Memory Palaces. According to the findings, this Mind Palace method is not only effective for memorizing words but also for enhancing idiomatic and collocational knowledge for English learners.
Keywords: Mind Palace, mnemonic, imagination, collocations, idioms, English language learners, method, foreign language, Method of Loci.